THE CORRELATION BETWEEN SELF-EFFICACY AND THESIS WORKING DURATION ON 2017 BIOLOGY EDUCATION STUDY PROGRAM STUDENTS DURING THE COVID-19 PANDEMIC AT UNIVERSITAS NEGERI MEDAN - Jihan Afifah Pasaribu; Meida Nugrahalia (Jurnal Pelita Pendidikan, 2023)
The purpose of this study is to determine the level of self-efficacy of students during a pandemic, the level of thesis working duration during a pandemic, and the relationship between self-efficacy and thesis working duration for students of the Biology Education Study Program Grade of 2017 at Universitas Negeri Medan during the Covid-19 pandemic. The descriptive method with a quantitative approach was used in this study. This study's population consisted of all students enrolled in the 2017 Biology Education study program at Universitas Negeri Medan. This study's sample size was 132 students, chosen using a simple random sampling technique. This study's instrument will be a questionnaire, with each questionnaire totaling 29 and 18 statements that have been declared valid and reliable. The results showed that students of the 2017 Biology Education study program at Medan State University had a self-efficacy level with a percentage value of 56.8% which was in the moderate category tending to be high, the level of thesis working duration with a percentage value of 70.5% owned by Biology Education 2017 students was in the moderate category tending to be low, and the results showed that there was a relationship between Self-efficacy and Thesis Working Duration in Biology Education 2017 students during the Covid-19 pandemic.